Capacity Building Needs of Business Education Lecturers for Efficient Lecturing in Federal Colleges of Education in North Western States, Nigeria - Abdulrazak Mohammed; Jibrin Haruna; Salisu Ladan (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2023)
The study empirically investigates how professional business education lecturers in Federal Colleges of Education in Nigeria's North-western needed to be strengthened. The study was guided by two research questions and two null hypotheses were formulated at 0.05 level of significance.  The study used a descriptive survey design. The population of this study was 126 professional business educators from six Federal Colleges of Education in North-western State, Nigeria. Research experts validated the instrument. The researchers used Cronbach Alpha method to determine the instrument's reliability and a reliability coefficient of 0.93 was then obtained. The questionnaire has 20 items in the instrument. The study used inferential statistics of mean and standard deviation to answer the research questions, while the t-test was used to test the null hypotheses formulated for the study. According to the study's findings, entrepreneurial skills, managerial skills, information and communication technology (ICT), and capacity building for professionalism are the priorities for all professional lecturers in the field of business education in federal colleges of education in North-western Nigeria. Based on the findings the researchers concluded that professional business education lecturers should be gingered because professionalism in Federal College Education necessitates ICT, managerial, and entrepreneurial competencies.   Keywords: Capacity building, Business education lecturers, Efficient lecturing